Moisture content of the sewage sludge dried using thermal dryer - Zakaria, M.S. (Asian Research Publishing Network, 2016)
Recently, the world's dependence on conventional fuels as the primary source of energy and the environmental impact as a consequence of utilizing these fuels, it is found that the use of renewable energy is in urgent need at the present time. Currently, utilization of biomass residue as a source of energy is becoming very promising as it not only reduces the dependence on fossil fuels and the related environmental impact but also assist in solving the long-term problems related to the disposal of these materials. The problem with as-received biomass residue is, however, the difficulty of use as a source of energy due to its high moisture content, low density and issues related with handling, storage and transportation. One of the ideal solution to dispose the sludge is by converting it into useful energy in form of solid fuel such as pallet and briquette. This solution not only solve the sludge disposal problem but also generate energy to mankind. However, the main problem faced in order to convert this sludge into energy is it contains high moisture content which is more than 90 of moisture content. In order to convert it into useful energy, the moisture content of the sludge need to reduce into acceptable level which is below 20. One of the method to remove the moisture content is by using thermal dryer. This paper discussing about the moisture content of the sewage sludge dried using the thermal dryer. The preliminary result obtain from the research found that the moisture content of the sewage sludge can be reduce up to 10.82 depending on the speed and the temperature of the dryer. Â© 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.